Efficient Construction of Chiral Spiro[benzo[g]chromene-oxindole] Derivatives via Organocatalytic Asymmetric Cascade Cyclization - Pan, Feng-Feng; Yu, Wei; Qi, Zheng-Hang; Qiao, Chunhua; Wang, Xing-Wang (Synthesis, 2014)
Pyranonaphthoquinone units are common in molecular structures with significant biological and pharmaceutical activities. Herein, the organocatalytic asymmetric cascade Michael cyclization reaction of 2-hydroxynaphthalene-1,4-diones to isatylidene malononitriles has been developed, which provided the desired spiro[4H-benzo[g]chromene-indoline] derivatives in up to 99% yield with up to 99% ee. To illustrate the potential utility of these products, a further transformation was conducted to give a spiropolyheterocyclic compound in moderate yield without loss of enantioselectivity (>99% ee). Biological evaluation of these spiro[benzo[g]chromene-indoline] derivatives has revealed excellent antiproliferative activity against a number of cancer cell lines, with a high inhibition rate ranging from 93% to 99% at a concentration of 50 μM.
Keywords: cascade cyclization; isatylidene malononitriles; hydroxynaphthalenes; spirobenzo[g]chromenes; spirooxindoles